Biological Staining and Culturing in Infectious Keratitis: Controversy in Clinical Utility - Moshirfar, Majid (Med Hypothesis Discov Innov Ophthalmol, 2019)
Infectious keratitis causes significant, financial burden and is only increasing in frequency with contact lens use. Despite this, no retrospective studies, prospective studies, or clinical trials have evaluated the diagnostic validity of clinical guidelines in cases of infectious keratitis. Currently, standard of care recommends that corneal samples be obtained for staining and culturing in select patients showing evidence of corneal ulceration. Ideally, diagnostic information from corneal sampling is thought to help guide therapeutic interventions, prevent disease progression, reduce antibiotic resistance, and decrease overall expenditures for the management and treatment of infectious keratitis. However, current staining and culturing methods are limited by poor sensitivity in non-bacterial cases (i.e. fungal, viral) and lengthy turnaround times, and these methods do not frequently change clinical decision making. Newer fluoroquinolones and broad-spectrum antibiotics resolve the vast majority of cases of infectious keratitis, rendering cultures less essential for management. We studied the clinical utility of obtaining corneal samples for culturing and staining and the need for future research to establish superior diagnostic guidelines for their use in infectious keratitis.